Indonesia's Development Diplomacy in Great Power Competition and ASEAN-Global South Interdependence 2025–2026 - Afipah, Septianis (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study analyzes Indonesia's development diplomacy strategy in response to the dynamics of the increasingly intense competition between the United States and China in the 2025 period until now. The transformation of the global development finance architecture—especially through the expansion of China's Belt and Road Initiative (BRI) and the United States' Partnership for Global Infrastructure and Investment (PGII)—has created a structural dilemma for developing countries in the Southeast Asian region. This study identifies a research gap in the form of a lack of studies that combine the perspective of complex interdependence (Keohane & Nye) with the reality of Indonesia's contemporary development policy post-2025 within the framework of South-South Cooperation. Using a qualitative policy analysis method with a comparative case study approach, this article argues that Indonesia strategically adopts an 'active hedging' posture in development diplomacy—utilizing dual membership in the G20, ASEAN, and BRICS+ as a platform to optimize development capital flows without getting caught up in bloc rivalries. The findings suggest that the complex interdependence framework significantly explains Indonesia's capacity to diversify development partnerships, but there are theoretical limitations in explaining the identity dimensions and norms in South-South policies. The policy implications lead to the need for institutionalization of stronger multilateral coordination mechanisms within the framework of the ASEAN Outlook on the Indo-Pacific (AOIP).